Multi-Spring Model and Pushover Analysis of Masonry-Infilled Wall in RC Frame Under Tsunami Loading - Foytong, Piyawat; Thanasisathit, Nuttawut; Ornthammarath, Teraphan; Tirapat, Supakorn; Prasomsri, Jitrakon; Nanongtum, Aphidet; Ruangrassamee, Anat; Chindaprasirt, Prinya (Civil Engineering Journal, 2025)
This study investigated the behavior of masonry-infilled walls (MIWs) within reinforced concrete (RC) frames when exposed to hydrodynamic forces from tsunamis by employing a multi-spring modeling approach across different inundation levels. The proposed analytical model divided the MIW into 1 to 5 horizontal nonlinear spring elements that were allocated along the wall's height. Each spring represented a segment of MIW and was defined by a tri-linear force–displacement relationship. The model was calibrated with the experimental data from previous studies and was analyzed using pushover assessment under uniformly distributed hydrodynamic forces corresponding to four tsunami inundation levels (0.25H, 0.50H, 0.75H, and 1.00H). The models, which had employed four or five horizontal springs, had most effectively replicated MIW behavior under tsunami loading at all inundation depths. Conversely, single-spring models tend to overestimate lateral resistance by up to 50%, particularly when the frame is only partially submerged. This discrepancy arises because less force is transmitted through the MIW, with a greater amount of it being transferred directly to the foundation. The utilization of several spring elements provided a realistic load path, improved the interaction between the frame and MIW characterization, and optimized the precision in simulating lateral resistance and post-peak behavior.